"I See No Other Option:" Maternal Practices of Sleep-Training and Co-Sleeping as the Management of Vulnerability. Issue 1 (1st August 2018) - Howson, Sara
This article proposes to investigate maternal practices concerning infant sleep from a feminist perspective, with particular attention to the growing critical interest in vulnerability. The topic of baby sleep and the practices that should be employed to manage it is one of the most controversial topics of paediatric research and parenting advice. It is also an issue that causes division between mothers. Opinion is polarised into two camps, one recommending independent sleep achieved through practices of sleep-training that involve leaving babies to cry; the other that encourages practices of 'co-sleeping' and attentive and responsive night-time care often achieved through mother and baby sharing a bed. In this article, I argue that both advocates of sleep-training and co-sleeping are seeking to offer neoliberally-informed individual solutions to social and political problems. I argue that baby sleep and the maternal practices employed to manage it have to be understood as strategies for managing human vulnerability in a culture and political environment that seeks to ignore it. I suggest that the debate between sleep-training and co-sleeping can be better understood through a consideration of care relations and the care deficit in post-industrial society. I argue that attention also needs to be given to discourses of medicalised childcare, and how the subject positions of mothers and babies are deeply troubled in a society where subjectivity is equated with independence.